2009
DOI: 10.2353/ajpath.2009.090525
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-Associated Antigen Expression in Lymphangioleiomyomatosis Renders Tumor Cells Susceptible to Cytotoxic T Cells

Abstract: The antibody HMB45 is used to diagnose lymphangioleiomyomatosis, a hyperproliferative disorder of lung smooth muscle cells with mutations in both alleles of either TSC1 or TSC2. A subset of these tumor cells expresses the melanoma-associated antigens gp100 and melanoma antigen recognized by T cells (MART-1). To explore the feasibility of targeting tumors in lymphangioleiomyomatosis by melanoma immunotherapy, we therefore assessed melanoma target antigen expression and existing immune infiltration of affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
(32 reference statements)
2
22
1
Order By: Relevance
“…Further studies confirmed the immunoreactivity of these structures with the HMB-45 antibody [22]. Some of the LAM cells also express a small transmembrane protein, melanoma-associated antigen recognized by T cells (MART-1), which is widely expressed in melanoma cells [23]. Both gp100 and MART-1 can be recognized by T cells, increasing the susceptibility of these cells to the cytotoxic activity of T cells.…”
Section: Lam Cell Phenotypementioning
confidence: 66%
See 1 more Smart Citation
“…Further studies confirmed the immunoreactivity of these structures with the HMB-45 antibody [22]. Some of the LAM cells also express a small transmembrane protein, melanoma-associated antigen recognized by T cells (MART-1), which is widely expressed in melanoma cells [23]. Both gp100 and MART-1 can be recognized by T cells, increasing the susceptibility of these cells to the cytotoxic activity of T cells.…”
Section: Lam Cell Phenotypementioning
confidence: 66%
“…This feature may become an important therapeutic target. Expression of tyrosinase-related proteins TRP-1 (gp-75) and TRP-2 was also observed in LAM cells [23]. Other markers of melanoma, such as CD63, a protein belonging to the tetraspanin family, or a recently described unknown protein which reacts with PNL2 antibody, are also present in LAM cells [24].…”
Section: Lam Cell Phenotypementioning
confidence: 97%
“…Although other melanosomal proteins have been investigated in LAM cells, the results appear more variable for proteins such as tyrosinase and tyrosinase-associated protein. 39,40 In addition, antimelanosomal-specifi c antibodies, or PNL2, 26 react with a large number of LAM lung nodules. However, LAM cells are more defi nitively identifi ed for their reactivity to HMB-45 and now a PEP13h.…”
Section: Resultsmentioning
confidence: 99%
“…Using tissue samples from subjects with LAM, the authors identified the expression of tyrosinase-related proteins (TRPs) 1 and 2 involved in melanogenesis in LAM samples in comparison to normal lung. Interestingly, the LAM nodules were densely infiltrated by macrophages but not dendritic cells or T cell subsets, demonstrating that LAM cell growth was not accompanied by enhanced immune infiltration (6). Further, cells dissociated from the LAM lung were susceptible to cytotoxic, gp100-reactive, and major histocompatibility complex class I restricted CD8 1 T cells, suggesting that immunotargeting gp100 provides beneficial cytotoxic effects on LAM cell growth.…”
Section: /2mentioning
confidence: 96%
“…SM-like LAM cells show high immunoreactivity for PCNA (proliferating cell nuclear antigen), a marker of DNA synthesis and cell proliferation, compared with the epithelioidlike HMB45-positive cells (2), suggesting that SM-like LAM cells represent the proliferative component of the LAM nodules. The role of melanocyte-specific markers in LAM and whether they could be targeted therapeutically have been explored (6) and were reviewed in the January issue (7).…”
mentioning
confidence: 99%